Farmers’ acceptance of insects as an alternative protein source in poultry feeds - Sebatta, C; Ssepuuya, G; Sikahwa, E; Mugisha, J; Diiro, G; Sengendo, M; Fuuna, P; Fiaboe, KKM; Nakimbugwe, D (International Journal of Agricultural Research, Innovation and Technology, 2018)
The research aimed at assessing the perceptions and willingness of poultry farmers, feed traders and processors to use insects as a source of protein ingredient in poultry feed. The research used a cross-sectional design and a structured questionnaire to collect quantitative data from 287 poultry farmers and 71 feed traders from 3 culturally diverse regions in Uganda. The study findings revealed that majority of the farmers mixed their own poultry feed. Willingness to use insects in poultry feeds was expressed by over 70% of the farmers, feed traders and processors, indicating a strong potential demand for insect-based feeds. However, some poultry farmers doubted the possibility of acquiring insects (rearing/harvesting) in large enough quantities and the consumers’ acceptance of poultry products from birds raised on insect-based feed. Nonetheless, there is a high potential for adoption of insects for use as poultry feed if they can be produced in sustainable quantities that ensure the viability of poultry farming and the feed processing businesses. Int. J. Agril. Res. Innov. & Tech. 8 (2): 32-41, December, 2018